Creative Conservation Risk Management: Evolving a Collection Risk Management Strategy at a Major Heritage Attraction. Issue 1 (March 2013) - Frame, Kate
This paper describes the development of a collection risk management strategy within Historic Royal Palaces, which is a thriving commercially-based visitor attraction. The approach is two pronged. It first comprises a steering body, the 'Agents of Decay' Board, for strategic direction and collaborative decision making for risk mitigation measures that are supported and implemented. Second, at operational level, it offers a team approach between conservators and commercial staff to achieve conservation risk management goals whilst delivering a financial and client or visitor successful business. Collection risk management is woven into the activities of the palaces enabling the Historic Royal Palace business to be successful, which in turn leads to the generation of more funds for conservation.